2013
DOI: 10.3389/fpubh.2013.00043
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Pilot Intervention for Community-Dwelling Adults with Rheumatoid Arthritis in Wuhan, China

Abstract: This study examined the effects of a pilot educational intervention program on knowledge, perceived self-efficacy, and health-related quality of life (HRQoL) of community-dwelling adults with rheumatoid arthritis (RA). A convenience sample of 16 participants with RA completed the program in Wuhan, China. Data were collected in face-to-face interviews using questionnaires at baseline, post-test, and 1 month follow-up. Knowledge scores were significantly increased over time. Significant differences were found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Also, 14% of patients felt that they lacked knowledge bDMARD biologic disease-modifying antirheumatic drug, BMI body mass index, csDMARD conventional synthetic disease-modifying antirheumatic drug, HCQ hydroxychloroquine, IQR interquartile range, LEF leflunomide, MTX methotrexate, NSAIDs nonsteroidal antiinflammatory drugs, RA rheumatoid arthritis, SASP salazosulfapyridine, SD standard deviation, tsDMARD targeted synthetic disease-modifying antirheumatic drug a Sum of n does not add up to 400 because patients may be prescribed two csDMARDs b Includes medication for RA and comorbidities or understanding of RA management. A pilot educational intervention study conducted in China revealed that the educational program on RA management not only significantly improved patients' knowledge but also their confidence in managing their disease effectively [27]. Though many reasons contribute to the differences in perceptions of AEs, our study suggests that it is important to optimize communication between patients and their rheumatologists to improve AE recognition and reporting, and the management of RA.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Also, 14% of patients felt that they lacked knowledge bDMARD biologic disease-modifying antirheumatic drug, BMI body mass index, csDMARD conventional synthetic disease-modifying antirheumatic drug, HCQ hydroxychloroquine, IQR interquartile range, LEF leflunomide, MTX methotrexate, NSAIDs nonsteroidal antiinflammatory drugs, RA rheumatoid arthritis, SASP salazosulfapyridine, SD standard deviation, tsDMARD targeted synthetic disease-modifying antirheumatic drug a Sum of n does not add up to 400 because patients may be prescribed two csDMARDs b Includes medication for RA and comorbidities or understanding of RA management. A pilot educational intervention study conducted in China revealed that the educational program on RA management not only significantly improved patients' knowledge but also their confidence in managing their disease effectively [27]. Though many reasons contribute to the differences in perceptions of AEs, our study suggests that it is important to optimize communication between patients and their rheumatologists to improve AE recognition and reporting, and the management of RA.…”
Section: Discussionmentioning
confidence: 68%
“…Also, 14% of patients felt that they lacked knowledge or understanding of RA management. A pilot educational intervention study conducted in China revealed that the educational program on RA management not only significantly improved patients’ knowledge but also their confidence in managing their disease effectively [ 27 ]. Though many reasons contribute to the differences in perceptions of AEs, our study suggests that it is important to optimize communication between patients and their rheumatologists to improve AE recognition and reporting, and the management of RA.…”
Section: Discussionmentioning
confidence: 99%
“…Sezgin's study showed predisposing factors were screening of the film at the ICU (Sezgin and Esin, 2018). The Deng study has referented the role of self-efficacy in the therapy of prophylactic behavior of rheumatoid arthritis (Deng and Hu, 2013). The mean score for studied factors before the intervention 1 and 2 were at low range, but after the intervention, significantly accelerated.…”
Section: Discussionmentioning
confidence: 99%
“… 52 Both group-based and individual-based educational programs with various modalities, such as face to face, telephone and internet, were successfully explored in the past 3 decades. 53 55 Cognitive-behavioral approach was used to enhance patient’s self-efficacy in these educational intervention programs. Specifically, four primary strategies have been suggested in clinical practice: 1) identify and facilitate patient’s performance accomplishments or skills mastery; 2) guide patient to observe vicarious experiences; 3) give social and verbal persuasion and 4) pay attention to patient’s physiological and emotional states.…”
Section: Discussionmentioning
confidence: 99%